Determinants of Urbanization - Anett Hofmann; Guanghua Wan (Asian Development Bank (ADB), 2013)
In light of the United Nations' (UN) latest urbanization projections, par- ticularly with respect to India and the People's Republic of China, a good understanding is needed of what drives aggregate urbanization trends. Yet, previous literature has largely neglected the issue in favor of studying urban concentration. Taking advantage of the latest UN World Urbanization Prospects, we use an instrumental variables approach to identify and analyze key urbanization determinants. We estimate the impact of gross domestic product (GDP) growth on urbanization to be large and positive. In answer to Henderson's (2003) finding that urbanization does not seem to cause growth, we argue that the direction of causality runs from growth to urbanization. We also find positive and significant effects of industrialization and education on urbanization, consistent with the existence of localization economies and labor market pooling.
hdl:11540/2310
Keywords: O18; R11; 330; urbanization; economic growth; education; industrialization